2021
DOI: 10.1186/s13584-021-00479-5
|View full text |Cite
|
Sign up to set email alerts
|

Dental health of preschool children after two-years of a supervised tooth brushing program in Southern Israel

Abstract: Background Supervised tooth brushing is an important part of leading national oral health improvement programs in different countries. With the cessation of water fluoridation in 2014, a new program was immediately required to provide community-based caries prevention, especially amongst young children. The aim of this study was to determine whether a supervised tooth brushing program (STBP) in kindergartens could reduce dental caries amongst preschool children, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This might indicate that although universal oral health coverage is an important step towards children's oral health improvement, there are other factors such as health literacy, health-related lifestyle and characteristics of care uptake and delivery which affect oral health status (13).…”
Section: Discussionmentioning
confidence: 99%
“…This might indicate that although universal oral health coverage is an important step towards children's oral health improvement, there are other factors such as health literacy, health-related lifestyle and characteristics of care uptake and delivery which affect oral health status (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that oral health risk behaviors (e.g., children's preference for sugar) and oral hygiene habits (e.g., tooth brushing frequency) could vary by children's sex 35 36 and age. 37 38 Based on this assumption, the child's sex and age (C) were added to DAG and created two non-causal paths in Fig. 1 as E←M→R←C→D (Model 3) and E←M→P←C→D (Model 4).…”
Section: Discussionmentioning
confidence: 99%